The Holistic Health Status of Chinese Homosexual and Bisexual Adults: A Scoping Review - Wu, Chanchan; Choi, Edmond Pui Hang; Chau, Pui Hing (Frontiers in Public Health, 2021)
Background: Same-sex marriage is currently not legalized in China, despite the considerably large number of homosexual and bisexual Chinese populations. At the same time, their holistic health status remains unclear. This is the first scoping review conducted to comprehensively examine all available literature and map existing evidence on the holistic health of homosexual and bisexual Chinese. Methods: This scoping review used the framework of Arksey and O’Malley and followed the PRISMA extension for scoping reviews. A comprehensive search strategy was carried out across 20 English and Chinese (both traditional and simplified) electronic databases from January 1, 2001 to May 31, 2020. Two reviewers conducted the reference screening and study selection independently and consulted a third senior reviewer whenever a consensus must be achieved. Data extraction was conducted using a structured data form based on the Cochrane template, after which a narrative synthesis of the findings was performed. Results: A total of 2,879 references were included in the ﬁnal analysis, with 2,478 research articles, 167 reviews, and 234 theses. Regarding the study populations, the vast majority of studies centered on men only (96.46%), especially men who have sex with men (MSM). Only 1.32% of the studies targeted female sexual minorities. The geographical distribution of all research sites was uneven, with most of them being conducted in mainland China (95.96%), followed by Hong Kong (2.05%), Taiwan (2.02%), and Macau (0.06%). Regarding the specific study focus in terms of the health domain, around half of the studies (45.93%) focused on sexual health only, and an additional quarter of studies (24.15%) investigated both sexual health and social well-being. Meanwhile, the studies focusing on mental health only accounted for about 15% of the total. Conclusions: This scoping review revealed that previous research focused more on male than female sexual minorities, on disease-centered surveys than person-centered interventions, and on investigations on negative health conditions than positive health promotion. Therefore, investigations centered on the female sexual minorities and corresponding person-centered interventions are highly needed.